Mexico - Income Generation and Social Protection for the Poor : Volume 4. A Study of Rural Poverty in Mexico - World Bank (Washington, DC, 2012)
This study is part of the second phase of a long-term programmatic work on poverty in Mexico, in three phases being carried out by the Bank at the request of the Government of Mexico. Reasons for a study on rural poverty, are because the size and intensity of the phenomenon, poverty, and inequality in rural Mexico are a matter of concern not only from the well-being of the poors' point of view, but also from that of the expansion of the internal market, inclusion of large sectors of the population traditionally excluded from the economic and social mainstream, and, the political integration and stability of the country. Poverty incidence in rural areas, in particular extreme poverty, is much higher than in urban ones. Although most of the country's moderate poor live in urban areas, most of the extreme poor are rural, even if the rural population is only one quarter of total. There are differences in sources of income between rural and urban poor. Also, rural environment poses specific constraints for provision of social infrastructure and services. Furthermore, institutions and culture tend to differ between rural and urban areas. The presence of indigenous groups is much larger in rural areas, whereas the production systems, the economic and other risks faced by rural poor and their coping strategies, usually largely differ from those of their urban peers. Mexico needs to move away from a fragmented social protection system, to a unified framework which nonetheless tailors different programs to different contexts in rural and urban areas. The study treats poverty as a multidimensional phenomenon intrinsically relative, with deep cultural aspects, and discusses the merits and limitations of quantifying poverty, in terms of measurable incomes and income lines. This report is organized as follows. Chapter 2 provides an overview of the evolution of poverty and inequality in the rural areas of Mexico in the decades between 1992 and 2002, while Chapter 3 looks more closely on what happened to rural incomes, employment, labor markets and the characteristics of rural labor force in the same period. Chapter 4 is devoted to examine the relation between poverty and the agricultural economy; Chapter 5 reviews the main agriculture, land and rural development policies and programs operating in Mexico, and examines them from the perspective of poverty friendliness; and, Chapter 6 starts with a theoretical discussion of the issues and challenges usually faced in the implementation of development policies and programs. Finally, Chapter 7 brings a more multidimensional and qualitative view, looking at how different types of rural poor can experience their poverty situation, including strategies to survive, manage risk and achieve petty accumulation, and, Chapter 8 concludes with a summary of policy options to reduce rural poverty in Mexico.